China's Spotted Sea Bass Aquaculture: Advances and Further Goals - Zhangfan Huang; Longhui Liu; Zhongbao Li (Reviews in Aquaculture, 2025)
Over the past two decades, China's spotted sea bass ( Lateolabrax maculatus ) aquaculture has flourished and made significant contributions to the national fishery economy. Characterized by a rapid growth rate and strong adaptability to various environmental conditions, this species also possesses the potential for global promotion in the aquaculture industry. The achievements in China's spotted sea bass aquaculture are inherently tied to progress in multidisciplinary knowledge and technology. To further catalyze the high‐quality development of the industry, a systematic review encompassing diverse research areas is imperative. This review encapsulates the advancements made in China's spotted sea bass aquaculture over the past two decades, and synthesizes decades of research progress encompassing germplasm management, seed production, breeding, nutrition, and common diseases. On this basis, it provides insights into the current challenges confronting the industry and highlights further goals for the industry's development. Such a review is not only of great significance for promoting the further systematic development of China's spotted sea bass aquaculture but also serves as a Chinese model for reference to the global promotion of spotted sea bass aquaculture practices.